IIUM Islamization Index - project report - Ahlan, Abdul Rahman; Kazeem, Bakare; Ajayi, Binyamin Adeniyi (2017)
Islamisation is seen as a process of conforming to the teachings of Islam in all aspect of human life by deconstructing and reconstructing the existing world view so that it can be in conformity with the dictates of Islam. Islamisation, being a debate among scholars sometimes is best assume as Islamisation with the suffix ‘ise’ to Islamise or better still as Islamicisation with the suffix ‘ice’ which may refer to action of conforming things into state of being Islamic. Islamicisation, thus connote the process of making knowledge and self to be Islamic. That is to say the process of making something to conform to the Islamic tenets as enshrined in the laws of Allah and explained by His last prophet. How IIUM community fared in this concept of conforming or harmonising other mundane knowledge with the revealed is becoming a necessity. Measurement of what has been achieved is a necessity that must be put into priority. Islamisation Index which can be traced to the concept of Islamisation of self and of human knowledge is a new index proposed to be used to measure the Islamic perspectives of the IIUM community.